Pengembangan Sistem Manajemen Layanan Pada Alisha Laundry Berbasis Web - Husnul Af Ali; Alfin Hidayat; Farizqi Panduardi (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2025)
Alisha Laundry, located at Pasar Wit-witan Alasmalang Singojuruh, faces challenges in managing day-to-day operations manually, including order management, scheduling, and customer service. This research aims to develop a web-based service management system to automate and integrate these processes, enhancing service quality and operational productivity. The system includes order management, pickup and delivery scheduling, real-time laundry tracking, and reporting modules. Utilizing the Laravel framework and Rapid Application Development (RAD) approach, the system improves operational efficiency and customer satisfaction by providing seamless online booking and tracking, thereby enhancing Alisha Laundry's competitiveness in the current digital era. With the implementation of this system, Alisha Laundry is expected to better respond to customer needs and expand their market share in an increasingly competitive industry. Moreover, the use of web technology enables management to make more informed decisions based on available data, providing long-term benefits for business growth and development.